Developmentally‐faithful and effective human erythropoiesis in immunodeficient and Kit mutant mice. Issue 9 (19th July 2017) - Fiorini, Claudia; Abdulhay, Nour J.; McFarland, Sean K.; Munschauer, Mathias; Ulirsch, Jacob C.; Chiarle, Roberto; Sankaran, Vijay G.
Abstract: Immunodeficient mouse models have been valuable for studies of human hematopoiesis, but high‐fidelity recapitulation of erythropoiesis in most xenograft recipients remains elusive. Recently developed immunodeficient and Kit mutant mice, however, have provided a suitable background to achieve higher‐level human erythropoiesis after long‐term hematopoietic engraftment. While there has been some characterization of human erythropoiesis in these models, a comprehensive analysis from various human developmental stages has not yet been reported. Here, we have utilized cell surface phenotypes, morphologic analyses, and molecular studies to fully characterize human erythropoiesis from multiple developmental stages in immunodeficient and Kit mutant mouse models following long‐term hematopoietic stem and progenitor cell engraftment. We show that human erythropoiesis in such models demonstrates complete maturation and enucleation, as well as developmentally appropriate globin gene expression. These results provide a framework for future studies to utilize this model system for interrogating disorders affecting human erythropoiesis and for developing improved therapeutic approaches.